Portrait of the artist as a young adult : the arts in young adult literature - Stover, Lois T.; Zitlow, Connie S., 1942- (Lanham : The Scarecrow Press, Inc., 2014)
"Young adults often struggle with confusion or guilt because they perceive themselves as different from others, especially their peers. For some of these individuals, the arts can help them cope with adolescent turmoil, allowing them to express their emotions in poems, stories, painting, songs, and other creative outlets. Sensitive teachers and parents know how important it is for young people to realize that they are not alone in their quest for self-knowledge and finding their way in the world. It can make a difference when readers find something in a book that helps them understand more about who they are and helps them understand others. In Portrait of the Artist as a Young Adult: The Arts in Young Adult Literature, Lois Thomas Stover and Connie S. Zitlow examine books in which the coming-of-age for young adults is influenced by the arts. Stover and Zitlow consider the connection between the arts and a young person's developing sense of self, the use of art to cope with loss and grief, and how young adults can use art to foster catharsis and healing. The young people in these books either identify as artists or use the arts in intentional ways to explore their identities. They often have artistic gifts that make them stand outside the norms of teenage life, yet those gifts also help them find a sense of community. Artists considered in this book include painters, photographers, sculptors, actors, directors, choreographers, dancers, composers, musicians, graffiti artists, and others. The books discussed also explore the ways adults can nurture the artist's development and understand the way young people sometimes use the arts to form their unique identity." -- Publisher's description.
Identity and the artist -- Crafting an identity as an artist -- The arts and loss -- The arts and solace: abandonment, abuse, and mental illness -- Friends, enemies, rivals, boyfriends and girlfriends -- Parents, teachers, and other mentors: adults as positive and negative influence on young artists -- Art and young adult literature: art in literature, literature about art, literature as art -- Appendix A: Annotated bibliography, young adult books about the arts -- Appendix B: using the arts pedagogically, moving students into and out of texts through arts-based strategies.
Includes bibliographical references and index.
Keywords: Young adult literature, American -- History and criticism; Young adult literature, English -- History and criticism; Artists in literature; Arts in literature; Artists in literature; Arts in literature; Young adult literature, American; Young adult literature, English; Criticism, interpretation, etc